AWWA's Water Quality Laboratory Committee Provides Resources for Operators. Issue 4 (4th May 2022) - Adams, Hunter; Holloway, Nicole
Abstract : You can take the plant operator out of the laboratory, but you can't completely remove the need for the laboratory from the operator. Plant operations are fundamentally tied to the laboratory. One of the goals of the AWWA Water Quality Laboratory Committee is to disseminate information that can be used by plant operators.